Malacofauna of Village Tanks and Minor SeasonalWater Bodies from Upper Deccan Plateau Ahmednagar Maharashtra - Sukhdeo, Pande Gajanan; S., Lonkar Rahul; Ashok, Rayate Dadasaheb; Ramsing, Patil Sachin (Asian Journal of Biological and Life Sciences)
Aim/Background: Tank irrigation is common in India and includes artificial water reservoirs such as village tanks, bandharas, and percolation tanks. The malacofauna of village tanks has been poorly documented. The present investigation is an attempt to make known the malacofauna of village tanks and minor water bodies from the upper part of Deccan Plateau Maharashtra. Materials and Methods: The mollusc specimens were collected from village tanks, and other minor seasonal water bodies from the 23 different localities within the study area. The specimens were preserved and subsequently identified by expert taxonomists at ZSI, WRS, and Pune. Results: The present study reports 19 mollusc species representing 7 families, and 12 genera. This includes 12 gastropods and 7 bivalves. The snail R. acuminata is found to be the most commonly distributed (78.3%) species in the study area. Data on species richness (S) shows that the Ghod River showed the highest value of 17 for species richness. Similarly, the Shannon-Weiner Species Diversity Index (H) is highest for the Ghod River. The value of H ranges between 0 to 2.86 for the water bodies studied. The species evenness (J) values range between 0 to 0.99. Conclusion: The study area harbours a number of economically important mollusc taxa. Many of the molluscs from the study area are of medical and veterinary importance. Some of them are used as food in the northeastern states of India. The snail A. carinata, a native species from the Australian continent, is reported from the study area for the first time.
Keywords: Diversity; Malacofauna; Village tanks